9 - -3 = 9 + 3 = 12 12 - 8 = 4 9 - -3 - 8 = 4
4/9 minus 3/4 equals -11/36
5/9 minus 2/3 equals -1/9
9
33
minus 21 think of it as 12+9 which equals 21 then just whack a minus sign infront
9 - -3 = 9 + 3 = 12 12 - 8 = 4 9 - -3 - 8 = 4
4/9 minus 3/4 equals -11/36
5/9 minus 2/3 equals -1/9
-3
If a equals 3 and b equals minus 5 then a minus b equals what
9
81
33
It is a quadratic equation and its solutions are: x = -3/2 and x = 3
[(1-4)/9] = [(-3)/9] = -1/3
3-(-9) Considering a negative plus a negative equals a positive your equation can be rewritten as 3+9 Which equals 12